Identification of skin bacterial profiles of early deceased bodies and the rto post-mortem interval - Chong, C.K.; Emamjomeh, M.; Joseph, N.; Siew, S.F.; Maeda, T.; Mustapha, N.A.; Hoshiko, Y.; Muthanna, A.; Amin-Nordin, S. (Malaysian Society for Parasitology, 2024)
Post-mortem microbiology (PMM) is an important tool in identifying possible causes of sudden unexpected death, as an infectious cause is highly suspected. However, contamination is a major problem in microbiology, and this has increased the difficulty determining the true pathogen that contributes to death in post-mortem cases. Skin commensals are common contaminants in blood cultures. This study was conducted to investigate the skin flora on early deceased bodies and observe the bacteria detected at different post-mortem intervals (PMIs). As blood is usually drawn from the neck and femoral sites for PMM examination, the two body sites were chosen as the sampling sites. Skin swab samples from the neck and femoral (n=80) of each early deceased body were collected by sterile cotton swabs. DNA was extracted from the swabs and then subjected to high-throughput 16S rRNA sequencing by using the Illumina MiSeq platform. Staphylococcus was found to be the most dominant genus in both neck and femoral sites. LEfSe results showed that Cutibacterium is significantly different at the neck site while Corynebacterium is more abundant at femoral site. There are significant differences at genus level between PMI<5H and PMI>5H at both neck and femoral sites. The findings of the present study may act as a reference for microbiologists and forensic pathologists when mixed growth or contamination occurs in post-mortem blood cultures.